Impact Of Smallholder Mining In Central Kalimantan - Vicki Dwi Purnomo; Noor Rahmat; Jumadi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Benefits of Gold Mining for Community Benefit in Parenggean District, and aims to determine gold mining practices by the community seen from the contracts used between laborers and landowners. This study uses a qualitative approach and the type of research is descriptive. Informants consist of the community. Collecting data with interviews and observation techniques. The results of this study indicate that gold mining practices in terms of contracts used between workers and landowners are in accordance with economic principles such as contracts made directly between landowners and workers. The contract was carried out by a reasonable party, there was a consent granted, but in terms of the object being contracted, namely gold on the surface of the earth, its existence cannot be ascertained.